Use of a Ketamine-Propofol Combination During Sedation and Analgesia - BAŞARANOĞLU, GÖKÇEN; Basaranoglu, GÖKÇEN; ESEN, ASIM; Esen, ASIM; BAKAN, Mefkur; TOPUZ, Ufuk; IDIN, Kadir; UMUTOGLU, Tarik (My University, 2015)
Aim: The aim of this study was to evaluate 1: 1 mixture of ketamine and propofol for sedative/analgesic efficacy, patient comfort and postoperative complications.
Keywords: Analgesia